N,N-dimetilglicina em dietas para frangos de corte - Boemo, Lenise Schroder (2012)
N,N-dimethylglycine (DMG) is intermediary metabolite in cellular choline to glycine metabolism, it is formed in the mitochondria of the liver by removing the group from betaine metil. The objective of this study was to determine the effect of dietary DMG in order to evaluate the performance and carcass characteristics of broilers. The experiment was carried out at the Federal University of Santa Maria Brazil. A total of 1920 1-day-old broiler (Cobb-500) were raised until 42 days of age. Birds were randomly assigned in three treatments with ten replicate pens of 64 birds each. It was used diets with two levels (0 or 1,000mg DMG/kg feed) and a diet with growth promoter (AGP). Diets were formulated based on corn and soybean meal. At 42days of age birds fed with diet with antibiotic had higher body weight broilers fed with control diet (P=0.0117), but the body weight of the birds and the BWG of antibiotic supplemented group did not differ. Feed intake at the end of the experimental period was lower in the birds of DMG supplemented than birds of antibiotic supplemented group. The study of carcass demonstrated effect of treatments. Birds fed with N,N-dimethylglycine had better carcass yield (74.98%) than birds without DMG (73.58%) in their diets (P=0.0195). Also this product increased the percentage of breast (P=0.0034) in 1.16% in relation birds fed without DMG and decreased the percentage of abdominal fat (P=0.0427) in 0.27% in relation to birds fed with AGP. Results of this studies suggest that the N,N-dimethylglycine (DMG) had positive effect on carcass characteristics of broilers.